PENGARUH MOTIVASI BELAJAR DALAM JARINGAN (DARING) MENGGUNAKAN GOOGLE CLASSROOM TERHADAP KETERAMPILAN MEMBACA SISWA KELAS XII MIPA MAN 1 BUNGO - Muryanti, S.Pd (Fokus | Jurnal Pendidikan STKIP YPM Bangko, 2022)
The purpose of this study was to describe the effect of online learning motivation using google classroom on the reading skills of class XII students of MAN 1 Bungo. This study uses a quantitative approach with a correlational method. The population of this study were all students of class XII MAN 1 Bungo, totaling 151 students. The number of samples was determined using the Slovin formula, with a precision of 10% obtained 100 students as samples. Sampling with simple random side technique by means of lottery. Collecting data using a questionnaire technique with instruments in the form of statements and tests with instruments in the form of question items. The normality test used the Kolmogorov-Smirnov formula with the results of the data being normally distributed and the linearity test using the F-test formula with the results of the variable having a linear pattern. Test the correlation hypothesis using the Pearson Product-Momment formula with rcount : 0.213 and rttable : 0.195. It turns out that rcount > rtable or 0.213 > 0.195. It turns out that rcount > rtable or 0.213 > 0.195.  The significance test using the Z-test obtained the value of Zcount : 2,119 and Ztable : 1.960, it turns out that Zcount > Ztable or 2.199 > 1.960. The contribution of the X variable to the Y variable was determined using the coefficient of determination formula with the results of 4.54% and 95.46% influenced by other factors. Thus, it can be concluded that there is a significant relationship between online learning motivation using google classroom and the reading skills of class XII students of MAN 1 Bungo for the 2020/2021 school year. The equation regression can be used to predict the value of reading skills based on a constant of 57.206 and a coefficient of 0.225 for learning motivation variables online (online) using google classroom.